Aerosol trapping filter membrane based on layered double hydroxides and preparation method of aerosol trapping filter membrane

By using layered bimetallic hydroxide (LDH) materials to prepare filter membranes, the problems of efficiency decline and short lifespan of existing aerosol capture membranes in high humidity environments are solved, achieving efficient capture of fine particulate matter and long lifespan, which is suitable for atmospheric pollutant monitoring and industrial waste gas treatment.

CN120860729APending Publication Date: 2025-10-31HANGZHOU INTERNATIONAL INNOVATION INSTITUTE OF BEIHANG UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511110457.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-08
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing aerosol capture membranes suffer from decreased efficiency, rapid material aging, and short service life in high humidity environments, and have low capture efficiency for fine particulate matter, resulting in high operating costs.

Method used

A filter membrane was prepared using layered bimetallic hydroxide (LDH) material. By adjusting the composition of metal elements and interlayer anions, the structure and performance were optimized, and the collection efficiency and stability were improved by combining surface functionalization treatment.

Benefits of technology

It efficiently captures fine particulate matter in high humidity environments, extends service life, reduces maintenance frequency and cost, and is suitable for air pollutant monitoring and industrial waste gas treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120860729A_ABST
    Figure CN120860729A_ABST
Patent Text Reader

Abstract

The invention discloses an aerosol trapping filter membrane based on layered double hydroxides as well as a preparation method and application of the aerosol trapping filter membrane, and aims to provide an aerosol trapping material which is efficient and stable and has good humidity adaptability. A filter membrane base material of the aerosol collection filter membrane is composed of an LDH membrane or an LDH-based composite membrane, and the LDH membrane or the LDH-based composite membrane can be subjected to surface functionalization treatment; and interlayer anions of the LDH are selected from laurate radicals or benzoate radicals. The invention also adopts an electrospinning technology to prepare an LDH nanofiber aerosol trapping filter membrane and an LDH and SiO2 composite aerosol trapping filter membrane. The LDH-based aerosol trapping filter membrane prepared by the method disclosed by the invention can still keep efficient PM2.5 and PM10 particle trapping capability for a long time in a high-humidity environment; and when the catalyst is applied to an industrial tail gas ventilation system, the long-time trapping rate can be maintained to be 96% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of atmospheric aerosols, specifically to an aerosol capturing filter membrane based on layered bimetallic hydroxide (LDH) material and its preparation method. Background Technology

[0003] Existing aerosol capture membranes are mainly made of materials such as cellulose, polyester, and glass fiber. Common filtration technologies include mechanical filtration, electrostatic precipitation, and adsorption. However, these membranes suffer from the following problems: poor humidity sensitivity; traditional membrane materials (such as polyester and glass fiber membranes) are prone to fiber expansion and adhesion in high-humidity environments, leading to a significant decrease in filtration efficiency, especially under rain and humidity conditions. Low capture efficiency; traditional membrane materials have low capture efficiency for fine particles (such as PM2.5); although efficiency can be improved by increasing the number of filter layers, too many layers increase airflow resistance, affecting filtration efficiency and permeability. Frequent material aging and replacement; existing membranes have a short lifespan, especially under high load and high humidity environments, where filtration efficiency deteriorates rapidly, requiring frequent maintenance and replacement, increasing operating costs.

[0004] Layered bimetallic hydroxides (LDHs) are a class of compound structures composed of layered metal ions (such as magnesium, aluminum, iron, and copper). They possess excellent physical and chemical stability, a large specific surface area, and good ion exchange capacity. LDH materials typically exhibit the following characteristics: Tunable structure: By adjusting the proportion of metal elements and the composition of interlayer anions, their physicochemical properties can be controlled, thus achieving designs with different functions. High specific surface area: Due to their layered structure, LDHs have a large specific surface area, providing more active sites, which is beneficial for the adsorption of gases and particulate matter. Good humidity adaptability: LDH materials maintain good structural stability and filtration efficiency in humid environments, showing significant advantages over traditional filter membrane materials (such as fiber materials and activated carbon). Summary of the Invention

[0005] In view of the above problems, the present invention provides an aerosol capturing filter membrane based on layered double hydroxide (LDH) material and its preparation method. This filter membrane can efficiently capture fine particulate matter such as PM2.5 and PM10, and has good anti-pollution performance, long service life, and excellent stability, making it suitable for use in atmospheric pollutant monitoring and air purification equipment.

[0006] To achieve the above-mentioned objectives, the technical solution of the present invention includes the following.

[0007] The present invention provides an aerosol collection filter membrane based on layered bimetallic hydroxide (LDH), wherein the filter membrane substrate of the aerosol collection filter membrane is composed of a layered bimetallic hydroxide (LDH) membrane or an LDH-based composite membrane.

[0008] Furthermore, the bimetallic elements constituting LDH are selected from any two of the following metal elements: magnesium (Mg), aluminum (Al), iron (Fe), calcium (Ca), zinc (Zn), nickel (Ni), cobalt (Co), copper (Cu), and iron (Fe). Filter membrane substrates composed of LDH or its composite membranes can achieve efficient capture of aerosols of different particle sizes by adjusting the ratio of metal elements and metal ions in the LDH.

[0009] Furthermore, the interlayer anion of LDH can be selected from chloride ions (Cl-). - LDH contains laurate, benzoate, etc. LDH has a layered structure with water molecules or anions between layers. The interlayer spacing is determined by the size and hydration level of the interlayer anions. The interlayer spacing can be adjusted by regulating the composition of the interlayer anions, thereby optimizing the aerosol collection efficiency and membrane permeability. Different metal ions and intercalated anions affect the collection efficiency and airflow permeability. For example, the LDH-based aerosol collection membranes prepared in Examples 2-3 of this invention are all MgAl-LDH films, and their processes are identical. The only difference is that laurate and benzoate were used as intercalated anions, respectively. Performance test results for collection efficiency and airflow permeability (pressure drop) show that membranes with different intercalated anions exhibit certain differences in pressure drop and collection efficiency.

[0010] Furthermore, the filter membrane substrate is an LDH membrane or an LDH-based composite membrane that has undergone surface functionalization treatment. The surface functionalization treatment method can be a physical or chemical method, including but not limited to electrostatic adsorption and chemical modification. For example, in Example 1, a chemical modification method was used to aminate the LDH nanofiber membrane filter membrane. Surface functionalization can improve the filter membrane's adsorption capacity for aerosol particles.

[0011] This invention also provides a method for preparing the above-mentioned LDH-based aerosol collecting filter membrane, including but not limited to using thin film preparation techniques such as sol-gel method and electrospinning method to obtain a uniform, structurally stable filter membrane with a high surface area. The preparation of the LDH-based aerosol collecting filter membrane includes at least two steps: the preparation of metal precursor LDH powder and the formation of LDH membrane or LDH-based composite membrane.

[0012] The preparation steps of the metal precursor LDH powder are as follows: A metal salt containing the metal element of LDH (such as magnesium chloride, aluminum chloride, etc.) is dissolved in deionized water, and the pH value is adjusted to a suitable range (usually 8-12) to promote LDH formation. Organic or inorganic anions (such as carbonate, sulfate, chloride, etc.) are added as interlayer anions. The metal precursor LDH powder is synthesized using solution methods such as co-precipitation, solvothermal methods, or calcination methods. For example, in solution methods, the metal salt solution is mixed with the anion source solution, and the pH is adjusted (usually using sodium hydroxide solution) to promote the precipitation reaction of LDH, resulting in layered bimetallic hydroxides; for example, the solvothermal method used in Example 1 of this invention is used to prepare the metal precursor LDH powder. The interlayer spacing and particle size of LDH are adjusted by controlling parameters such as reaction temperature, time, and pH value. Alternatively, the metal precursor can be prepared using a calcination method, as in Example 5.

[0013] The formation of LDH membranes or LDH-based composite membranes involves preparing uniform LDH thin films or LDH-based composite membranes from solutions of synthesized LDH powder using electrospinning or coating methods. For example, in Examples 1-4, LDH fiber membranes were formed from solutions of LDH powder using electrospinning. Electrospinning can yield nanoscale LDH fiber membranes with high specific surface area and good air permeability.

[0014] Furthermore, during the membrane formation process, LDH is combined with other materials to form an LDH-based composite membrane. The composite membrane formation process is not limited to any specific membrane-forming method. For example, in Example 5, a coating method is used to coat a solution of LDH powder and SiO2 precursor onto a polyester-based membrane to form an LDH-SiO2 composite membrane. This membrane is then further laminated with a polyurethane membrane to form the final LDH-based aerosol collection filter membrane, thereby improving the mechanical properties of the filter membrane and the flexibility and weather resistance of the membrane structure.

[0015] The method for preparing the above-mentioned aerosol collecting filter membrane may further include a step of surface functionalization treatment of the prepared LDH membrane or LDH-based composite membrane. For example, conductive materials (such as carbon nanotubes, conductive polymers, etc.) can be introduced onto the surface of the LDH membrane or composite membrane by electrospinning or chemical methods to enhance its adsorption capacity for charged aerosols. Alternatively, various functional groups, such as amino and hydroxyl groups, can be introduced onto the surface of the filter membrane by chemical modification to improve the membrane's affinity for different types of aerosols. For example, the LDH membrane in Example 1 of this invention has undergone surface amylation.

[0016] Compared with existing technologies, the technical solution of this invention allows for the flexible design of filter membranes with different performance characteristics by adjusting the types of metal ions and interlayer anions in LDH, meeting the needs of different environments and applications. This invention can be used for aerosol capture; LDH filter membranes can efficiently capture fine particulate matter in the air, such as PM2.5 and PM10, especially in high-humidity environments. LDH materials, with their highly adjustable layered structure and large specific surface area, can efficiently capture fine particulate matter. In environmental monitoring, this filter membrane can be used in air pollutant monitoring equipment, ensuring long-term stable operation with a long service life and low maintenance costs. For industrial waste gas treatment, LDH filter membranes can be used in emission monitoring systems to capture particulate matter or pollutants in industrial gases. LDH materials have good adaptability to environmental factors such as humidity and temperature, making them suitable for complex climatic conditions, especially high-temperature and high-humidity industrial environments. Attached Figure Description

[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly introduced below. The features and advantages of the present invention can be more clearly understood by referring to the accompanying drawings. The accompanying drawings are schematic and should not be construed as limiting the present invention in any way. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0018] Figure 1 This is a schematic diagram of the aerosol capture filter membrane collection efficiency testing device for various embodiments and comparative examples of the present invention.

[0019] In the diagram: 1 is the airflow inlet, 2 is the LDH-based aerosol capture filter membrane, 3 is the airflow outlet, 4 is the filter support, and 5 is the pollutant particles.

[0020] Figure 2 The graph in the middle shows the PM2.5 particle capture efficiency of the LDH-based composite aerosol collecting filter membrane prepared in Example 5 and the filter membranes of Comparative Examples 1 and 2 under high humidity (80%) conditions and the performance changes after 24 hours of use. Detailed Implementation

[0021] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.

[0022] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention. Example 1

[0023] In this embodiment, a MgAl-LDH aerosol collecting filter membrane with lauric acid anion intercalation was prepared, and its surface was further functionalized.

[0024] Step 1, Solution preparation: According to the molar ratio M 3+ :M 2+ In a 3:1 ratio, 6.16 g of Mg(NO3)2·6H2O and 3 g of Al(NO3)3·9H2O were dissolved together in 100 mL of deionized water, and this solution is designated as Solution 1. 1.5 g of NaOH and 0.008 mol of sodium laurylate were used to prepare an 80 mL aqueous solution, which was then activated by heating and stirring at 40 °C for 20 min using a magnetic stirrer, and this solution is designated as Solution 2. 8 g of NaOH was dissolved in 80 mL of deionized water for subsequent reaction to adjust the pH value, and this solution is designated as Solution 3.

[0025] Step 2, Preparation of LDH powder by hydrothermal coprecipitation: Transfer Solution 1 to a 500 mL three-necked flask and place it on an electric constant-temperature oil bath for heating and stirring. Nitrogen gas is bubbled into the solution to prevent CO2 from the air from entering and causing CO3. 2- Insert a thermometer into the LDH interlayer. When the temperature reaches 95 ℃, insert a glass funnel and maintain a constant temperature. Add the prepared solution 2 dropwise through the glass funnel at a rate of one to two drops per second. After the addition is complete, adjust the pH value to 10 using solution 3, and then continue stirring at 95 ℃ for 1-2 hours. Pour the completed reaction solution into a 200 mL polytetrafluoroethylene (PTFE) liner. Place the PTFE liner into an autoclave, tighten the autoclave, and place the apparatus in an electric forced-air drying oven at 125 ℃ for 24 hours. After removing the autoclave and allowing it to cool to room temperature, filter, wash, and dry the reaction solution, or centrifuge, wash, and dry to obtain a MgAl-LDH powder sample with lauric acid intercalation. The sample should be washed twice with water and three times with alcohol.

[0026] Step 3, LDH film preparation: The synthesized LDH powder was dissolved in a water-ethanol mixed solvent to form a 5 wt% LDH solution. To enhance the electrospinning properties of the fibers, a polymer concentration of approximately 8 wt% polyvinyl alcohol (PVA) was added to increase the solution viscosity and aid fiber formation. The electrospinning voltage was set at 20 kV, the distance between the nozzle and the collecting plate was set at 15 cm, the solution flow rate was 1 mL / h, the collecting plate rotation speed was 500 rpm, the temperature was set at 25℃, and the humidity was controlled at 45%. The prepared LDH film achieved a fiber diameter of 100-300 nm.

[0027] Step 4, Surface Functionalization Treatment: The prepared LDH nanofiber film is immersed in an ethanol solution of 1.5% APTES. The reaction is carried out at room temperature for 2 hours, or by heating at 50-60 °C. The film is thoroughly washed with deionized water and dried to obtain an aminated LDH nanofiber film, thus obtaining the surface-aminated MgAl-LDH aerosol collecting filter membrane with lauric acid anion intercalation in this embodiment.

[0028] In this embodiment, the prepared MgAl-LDH aerosol collecting filter membrane underwent surface functionalization treatment, specifically amylation of the filter membrane surface. On one hand, the amylated functional layer enhances electrostatic adsorption in the filter membrane: amino groups readily protonate into positive charges (—NH3) in air. + Amino groups can electrostatically attract negatively charged aerosol particles in the atmosphere (such as PM2.5 containing nitrates and sulfates), improving the membrane's capture efficiency for particulate matter. They also enhance the membrane's surface affinity and chemisorption capacity. Amino groups possess polarity and hydrophilicity, allowing them to form hydrogen bonds or dipole interactions with polar organic compounds (such as aldehydes, ketones, aromatic hydrocarbons, and some VOCs), thereby strengthening the membrane's adsorption performance for organic aerosols. Furthermore, amino groups readily react with other functional groups (such as carboxyl and aldehyde groups), providing a platform for subsequent multifunctional modification. Therefore, they can serve as anchor sites for further chemical modification, potentially enabling the membrane to possess extended functions such as antibacterial, catalytic, and photoresponsive properties.

[0029] Aerosol collection experiments were conducted on the MgAl-LDH aerosol collecting filter membrane prepared in this embodiment: Under laboratory conditions, using methods such as... Figure 1 The device shown simulates the capture effect of PM2.5 particles on the filter membrane, such as... Figure 1As shown, the test airflow enters the closed airflow channel of the device through the airflow inlet 1. Several filter supports 4 are installed on the airflow channel, and a single-layer LDH aerosol capturing filter membrane with an area of ​​50 mm × 50 mm is installed on the filter support. The airflow passes sequentially through the LDH aerosol capturing filter membrane 2 on each filter support 4 along the channel. As shown in the figure, several pollutant particles 5 in the airflow are adsorbed by the LDH aerosol capturing filter membrane and finally flow out of the test device from the airflow outlet 3 located on the other side of the airflow channel. The gas flowing out of the airflow outlet 3 is collected. By comparing the particle content in the gas before entering the airflow inlet and the gas flowing out of the airflow outlet, the collection efficiency of the single-layer LDH aerosol capturing filter membrane is calculated. The results show that the LDH nanofiber membrane, i.e., the MgAl-LDH aerosol collecting filter membrane, prepared in this embodiment can still effectively capture more than 99% of PM2.5 particles under a humidity of 80%. Moreover, under 48 hours of continuous collection, the PM2.5 collection efficiency of the LDH nanofiber membrane remains above 98.7%. The results of the test at an airflow of 5 L / min show that under 48 hours of continuous collection, the pressure drop increased from 92 Pa to 96 Pa, but the change in pressure drop was not significant, indicating that the membrane material has good particle load-bearing capacity and structural stability. Example 2

[0030] This embodiment prepares a MgAl-LDH aerosol collecting filter membrane with lauric acid anion intercalation.

[0031] Step 1, Solution preparation: According to the molar ratio M 3+ :M 2+ In a 3:1 ratio, 6.16 g of Mg(NO3)2·6H2O and 3 g of Al(NO3)3·9H2O were dissolved together in 100 mL of deionized water, and this solution is designated as Solution 1. 1.5 g of NaOH and 0.008 mol of sodium laurate were used to prepare an 80 mL aqueous solution, which was then activated by heating and stirring at 40 °C for 20 min using a magnetic stirrer, and this solution is designated as Solution 2. 8 g of NaOH was dissolved in 80 mL of deionized water for subsequent reaction to adjust the pH value, and this solution is designated as Solution 3.

[0032] Step 2, Preparation of LDH powder by hydrothermal coprecipitation: Transfer Solution 1 to a 500 mL three-necked flask and heat and stir in an electric constant-temperature oil bath. Nitrogen gas is bubbled into the solution to prevent CO2 from the air from entering and causing CO3. 2-Insert a thermometer into the LDH interlayer. When the temperature reaches 95 ℃, insert a glass funnel and maintain a constant temperature. Add the prepared solution 2 dropwise through the glass funnel at a rate of one to two drops per second. After the addition is complete, adjust the pH value to 10 using solution 3, and then continue stirring at 95 ℃ for 1-2 hours. Pour the completed reaction solution into a 200 mL polytetrafluoroethylene (PTFE) liner. Place the PTFE liner into an autoclave, tighten the autoclave, and place the apparatus in an electric forced-air drying oven at 125 ℃ for 24 hours. After removing the autoclave and allowing it to cool to room temperature, filter, wash, and dry the reaction solution, or centrifuge, wash, and dry to obtain a MgAl-LDH powder sample with lauric acid intercalation. The sample should be washed twice with water and three times with alcohol.

[0033] Step 3, LDH membrane preparation: The synthesized LDH powder was dissolved in a water-ethanol mixed solvent to form a 5 wt% LDH solution. To enhance the electrospinning properties of the fibers, 8 wt% polyvinyl alcohol (PVA) was added to increase the solution viscosity and aid fiber formation. The electrospinning voltage was set at 20 kV, the distance between the nozzle and the collecting plate was set at 15 cm, the solution flow rate was 1 mL / h, the collecting plate rotation speed was 500 rpm, the temperature was set at 25℃, and the humidity was controlled at 45%. This resulted in an LDH membrane with a fiber diameter of 100-300 nm, which is the LDH aerosol collecting filter membrane prepared in this embodiment. Example 3

[0034] This embodiment prepares a MgAl-LDH aerosol collecting filter membrane with benzoic acid anion intercalation. Compared with Example 3, the MgAl-LDH aerosol collecting filter membrane prepared in this embodiment only changed the anion intercalation layer, replacing the intercalated anion with benzoic acid anion instead of lauric acid anion.

[0035] Step 1, Solution preparation: According to the molar ratio M 3+ :M 2+ In a 3:1 ratio, 6.16 g of Mg(NO3)2·6H2O and 3 g of Al(NO3)3·9H2O were dissolved together in 100 mL of deionized water, and this solution is designated as Solution 1. 1.5 g of NaOH and 0.008 mol of sodium benzoate were used to prepare an 80 mL aqueous solution, which was then activated by heating and stirring at 40 °C for 20 min using a magnetic stirrer, and this solution is designated as Solution 2. 8 g of NaOH was dissolved in 80 mL of deionized water for subsequent reaction to adjust the pH value, and this solution is designated as Solution 3.

[0036] Step 2, Preparation of LDH powder by hydrothermal coprecipitation: Transfer Solution 1 to a 500 mL three-necked flask and heat and stir in an electric constant-temperature oil bath. Nitrogen gas is bubbled into the solution to prevent CO2 from the air from entering and causing CO3. 2- Insert a thermometer into the LDH interlayer. When the temperature reaches 95 ℃, insert a glass funnel and maintain a constant temperature. Add the prepared solution 2 dropwise through the glass funnel at a rate of one to two drops per second. After the addition is complete, adjust the pH value to 10 using solution 3, and then continue stirring at 95 ℃ for 1-2 hours. Pour the completed reaction solution into a 200 mL polytetrafluoroethylene (PTFE) liner. Place the PTFE liner into an autoclave, tighten the autoclave, and place the apparatus in an electric forced-air drying oven at 125 ℃ for 24 hours. After removing the autoclave and allowing it to cool to room temperature, filter, wash, and dry the reaction solution, or centrifuge, wash, and dry to obtain a MgAl-LDH powder sample with benzoic acid anion intercalation. The sample should be washed twice with water and three times with alcohol.

[0037] Step 3, LDH membrane preparation: The synthesized LDH powder was dissolved in a water-ethanol mixture to form a 5 wt% LDH solution. To enhance the electrospinning properties of the fibers, 8 wt% polyvinyl alcohol (PVA) was added to increase the solution viscosity and aid fiber formation. The electrospinning voltage was set at 20 kV, the distance between the nozzle and the collecting plate was set at 15 cm, the solution flow rate was 1 mL / h, the collecting plate rotation speed was 500 rpm, the temperature was set at 25℃, and the humidity was controlled at 45%. This resulted in an LDH membrane with a fiber diameter of 100-300 nm, which is the LDH aerosol collecting filter membrane prepared in this embodiment. Example 4

[0038] This embodiment prepares a MgAl-LDH aerosol collecting filter membrane with chloride ion intercalation. Compared with Example 3, the MgAl-LDH aerosol collecting filter membrane prepared in this embodiment only changed the anion intercalation layer, replacing the intercalated anion with chloride ions instead of laurate anions.

[0039] Step 1, Preparation of the metal precursor solution: According to the molar ratio M 3+ :M 2+In a 3:1 ratio, 6.16 g of Mg(NO3)2·6H2O and 3 g of Al(NO3)3·9H2O were dissolved together in 100 mL of deionized water, and this solution is designated as Solution 1. 1.5 g of NaOH and 0.008 mol of sodium chloride were used to prepare an 80 mL aqueous solution, which was then activated by heating and stirring at 40 °C for 20 min using a magnetic stirrer, and this solution is designated as Solution 2. 8 g of NaOH was dissolved in 80 mL of deionized water for subsequent reaction to adjust the pH value, and this solution is designated as Solution 3.

[0040] Step 2, Preparation of LDH powder by hydrothermal coprecipitation: Transfer Solution 1 to a 500 mL three-necked flask and heat and stir in an electric constant-temperature oil bath. Nitrogen gas is bubbled into the solution to prevent CO2 from the air from entering and causing CO3. 2- Insert a thermometer into the LDH interlayer. When the temperature reaches 95 °C, insert a glass funnel and maintain a constant temperature. Add the prepared solution 2 dropwise through the glass funnel at a rate of one to two drops per second. After the addition is complete, adjust the pH value to 10 using solution 3, and then continue stirring at 95 °C for 1-2 hours. Pour the completed reaction solution into a 200 mL polytetrafluoroethylene (PTFE) liner. Place the PTFE liner into an autoclave, tighten the autoclave, and place the apparatus in an electric forced-air drying oven at 125 °C for 24 hours. After removing the autoclave and allowing it to cool to room temperature, filter, wash, and dry the reaction solution, or centrifuge, wash, and dry to obtain a MgAl-LDH powder sample with chloride ion intercalation. The sample should be washed twice with water and three times with alcohol.

[0041] Step 3, LDH membrane preparation: The synthesized LDH powder was dissolved in a water-ethanol mixture to form a 5 wt% LDH solution. To enhance the electrospinning properties of the fibers, 8 wt% polyvinyl alcohol (PVA) was added to increase the solution viscosity and aid fiber formation. The electrospinning voltage was set at 20 kV, the distance between the nozzle and the collecting plate was set at 15 cm, the solution flow rate was 1 mL / h, the collecting plate rotation speed was 500 rpm, the temperature was set at 25℃, and the humidity was controlled at 45%. This resulted in an LDH membrane with a fiber diameter of 100-300 nm, which is the LDH aerosol collecting filter membrane prepared in this embodiment.

[0042] The LDH-based aerosol collection membrane of this invention utilizes the different anion selections and interlayer spacings between layers in the LDH layered structure, which influences the collection efficiency and airflow permeability. For example, the LDH-based aerosol collection membranes prepared in Examples 2-4 above are all MgAl-LDH films, differing only in that the intercalated anions used are laurate, benzoate, and chloride ions, respectively. Figure 1 The test apparatus was used to test the aerosol collection efficiency. The PM2.5 collection efficiency and pressure drop performance were tested at 80% relative humidity. The test results showed that different intercalated anion filter membranes exhibited certain differences in pressure drop and collection efficiency. However, overall, under 80% high humidity conditions, the aerosol collection efficiency of the LDH-based filter membrane was still better than that of conventional filter membranes under the same conditions. For example, Table 1 below lists the collection efficiency and pressure drop test results of two different intercalated anion-based LDH filter membranes from Examples 2 and 3. Pressure drop refers to the pressure difference per unit area of ​​the filter membrane, reflecting its permeability; a lower pressure drop indicates better permeability. The test condition was an airflow rate of 5 L / min.

[0043] Table 1 Example Intercalated anions Particle size range (PM) Relative humidity (%) Capture efficiency (%) Pressure drop (Pa) Example 2 Laurate PM2.5 80 98.7 95 Example 3 Benzoate PM2.5 80 96.2 82 Example 5

[0044] This embodiment prepares an LDH-based composite aerosol collection filter membrane.

[0045] Step 1, Configuration of the metal precursor LDO: According to the molar ratio M 3+ :M 2+ A mixture of 6 g Ca(NO3)2·6H2O and 3.18 g Al(NO3)3·9H2O in a 3:1 ratio is dissolved in 100 mL of deionized water, and this solution is labeled as solution 1. 1.5 g of NaOH is used to prepare an 80 mL aqueous solution, labeled as solution 2. 8 g of NaOH is dissolved in 80 mL of deionized water for subsequent pH adjustment, labeled as solution 3. Solution 1 is transferred to a 500 mL three-necked flask and heated with stirring in an electric constant-temperature oil bath. Nitrogen gas is bubbled into the solution to prevent CO2 from the air from entering and causing CO32-. 2- Insert a thermometer into the LDH interlayer. When the temperature reaches 95 °C, insert a glass funnel and maintain a constant temperature. Add the prepared solution 2 dropwise through the glass funnel at a rate of one to two drops per second. After the addition is complete, adjust the pH to 10 using solution 3, and then continue stirring at 95 °C for 1-2 hours.

[0046] Step 2, calcination method for preparing LDH powder: Pour the completed reaction solution into a 200 mL polytetrafluoroethylene (PTFE) liner. Place the PTFE liner into an autoclave, tighten the autoclave, and place the apparatus in an electric forced-air drying oven at 125 °C for 24 hours. After cooling to room temperature, filter, wash, and dry the reaction solution, or centrifuge, wash, and dry to obtain the LDH precursor powder sample. Wash twice with water and three times with alcohol. Place the obtained precursor powder sample in a muffle furnace and calcine at 500 °C for 3 hours to obtain LDO. Then, add 0.008 mol of sodium benzoate and 1.5 g of NaOH to 80 mL of deionized water to prepare solution 4. Add 0.5 g of LDO and 80 mL of solution 4 to a three-necked flask. Purge the solution with nitrogen gas to prevent CO2 from entering the solution and causing CO32-. 2- Entering the LDH interlayer, the pH value was adjusted to 10, and the reaction was stirred for 2 h under 95 ℃ oil bath conditions. The obtained sample was centrifuged, washed, and dried to obtain CaAl-LDH powder with benzoate intercalation.

[0047] Step 3, Preparation of LDH-SiO2 Composite Membrane: Tetraethyl orthosilicate (TEOS) was used as the SiO2 precursor. An appropriate amount of acid (such as hydrochloric acid or acetic acid) was added as a catalyst to adjust the pH to 4-5, promoting hydrolysis and condensation reactions to obtain SiO2 sol. The obtained SiO2 sol was hydrothermally treated at 60 °C for 2 h to promote further SiO2 reaction. The prepared CaAl-LDH powder and SiO2 sol were mixed in a 2:1 ratio, stirred evenly, and reacted at 75 °C for 2 h to form a homogeneous composite solution. The composite solution was uniformly coated onto a polyester film substrate using a spin-coating method. The spin-coating speed was typically 2000 rpm, and the spin-coating time was 40 s. The coated composite membrane was then dried in a 130 °C oven for 2 h to remove the solvent and promote membrane densification. After drying, the LDH-SiO2 composite membrane was obtained.

[0048] Step 4, Lamination of polyurethane membrane and LDH-SiO2 composite membrane: A 100 μm thick thermoplastic polyurethane (TPU) was selected as the bottom layer membrane. The LDH-SiO2 composite membrane and the polyurethane membrane were aligned and laminated using a hot press. The temperature was controlled at 120 °C, the pressure at 3 MPa, and the lamination time at 6 min. After lamination, the membrane was cooled to room temperature to obtain the LDH-based composite aerosol collection filter membrane of this embodiment.

[0049] The LDH-based composite aerosol collecting filter membrane prepared in this embodiment uses conventional polyester film (PET) as the base layer to provide basic physical support for the LDH-based composite filter membrane, ensuring stable adhesion of the LDH-SiO2 composite layer, maintaining overall flexibility and stability, and facilitating roll forming and equipment integration. The combination of LDH and SiO2 provides a network framework for LDH, enhancing the membrane's thermal stability and mechanical strength, improving coating uniformity and structural density, and forming a porous / nano-network structure after composite with LDH. This facilitates gas permeability, increases collection paths, and improves the membrane's wear resistance and continuous operation capability. Furthermore, the TPU laminated protective layer provides mechanical protection for the composite membrane, improving the overall membrane structure's flexibility and weather resistance, preventing membrane peeling or cracking, and delaying structural fatigue during long-term use. In this embodiment, LDH is the most important functional layer of the LDH-based composite aerosol collecting filter membrane. LDH provides electrostatic adsorption, surface adsorption and chemical fixation capabilities for charged aerosol particles (such as PM2.5) and some organic pollutants. Due to its high specific surface area and tunable interlayer anionic structure, it is beneficial to maintain the collection efficiency under high humidity conditions. LDH significantly improves the effective collection capacity of the filter membrane for PM2.5 and PM10, and also has a certain VOC adsorption effect.

[0050] The inventors verified through the following tests that the LDH-based composite aerosol collecting filter membrane prepared in this embodiment exhibits high collection efficiency and anti-pollution capability when applied to industrial waste gases, making it suitable for highly polluted environments such as metallurgy and chemical industries. The specific test process and results are as follows.

[0051] To verify the collection performance and structural stability of the LDH-based composite aerosol collecting filter membrane prepared in this embodiment under high temperature, high humidity, and multiple pollution loads, the inventors built a simulated industrial exhaust gas ventilation system in the laboratory and set the following environmental parameters: ambient temperature set at 55 ℃, relative humidity set at 85%, and particulate matter set at PM2.5 (200 μg / m³). 3 PM10 (300 μg / m³) 3 The gaseous pollutants were SO2 (30 ppm) and NO. x After 72 hours of continuous operation with 25 ppm of toluene (50 ppm), the LDH-based composite aerosol collecting filter membrane of this embodiment can still maintain a high PM2.5 collection rate of over 96% under high temperature (55 ℃), high humidity (85 % RH) and complex gaseous pollutant conditions. The pressure drop changes from the initial 108 Pa to 121 Pa, and the pressure drop change is stable. No obvious blockage or structural damage is observed on the membrane surface, indicating that it has excellent thermal stability, structural retention and anti-pollution ability, and is suitable for industrial waste gas scenarios.

[0052] Comparative Example 1 The aerosol collection filter membrane in this comparative example is a conventional polyester film. This polyester film is the polyester base membrane used as the coating substrate in step 3 of the preparation of the LDH-based composite aerosol collection filter membrane in Example 5. This membrane is also one of the commonly used aerosol collection filter membranes.

[0053] Comparative Example 2 The aerosol collection filter membrane used in this comparative example is a conventional commercially available HEPA-grade glass fiber filter membrane, which is also one of the commonly used aerosol collection filter membranes.

[0054] The performance of the LDH-based aerosol collection filter membranes of various embodiments of the present invention and the conventional aerosol filter membranes in the comparative examples were compared and tested. The test conditions were as follows: each filter membrane of each embodiment and the comparative example was cut into 50 mm × 50 mm samples and placed in a... Figure 1 In the aerosol testing apparatus shown, the test airflow rate is 5 L / min, the test humidity condition is 80% RH, the test temperature is 25 ℃, and the particulate matter source is PM2.5 (200 μg / m³). 3 ) and PM10 (300 μg / m 3 The test lasted for 24 consecutive hours. The test results confirmed that the LDH-based filter membranes of the various embodiments of the present invention exhibited superior performance compared to the conventional filter membranes in the comparative examples in terms of capture efficiency, structural stability, moisture resistance, and pressure drop control. For example, as... Figure 2 The figure shows the PM2.5 particle capture efficiency of the LDH-based composite aerosol collecting filter membrane prepared in Example 5 and the filter membranes of Comparative Examples 1 and 2 under high humidity (80%) conditions, as well as the performance changes after 24 hours of use. As can be seen from the figure, the LDH-based composite aerosol collecting filter membrane of Example 2 has a collection efficiency higher than 96%, and it maintains stable permeability even after 24 hours, with a collection efficiency still above 96%. In contrast, the collection performance of the conventional polyester membrane and glass fiber membrane in the comparative examples shows a significant decrease. The data in the figure demonstrates that the LDH-based aerosol collecting filter membrane of this invention exhibits superior performance in terms of collection efficiency, structural stability, moisture resistance, and pressure drop control.

[0055] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Other variations and modifications are possible without departing from the technical solutions described in the claims.

Claims

1. An LDH-based aerosol collection filter membrane, characterized in that: The filter substrate of the aerosol collecting filter membrane is composed of an LDH membrane or an LDH-based composite membrane.

2. The LDH-based aerosol collection filter membrane according to claim 1, characterized in that: The bimetallic elements constituting the LDH are selected from any two of magnesium, aluminum, iron, calcium, zinc, nickel, cobalt, copper, and iron.

3. The LDH-based aerosol collection filter membrane according to claim 1, characterized in that: The interlayer anion of the LDH is selected from chloride ions, laurate ions, or benzoate ions.

4. The LDH-based aerosol collection filter membrane according to claim 1, characterized in that: The filter membrane substrate is an LDH membrane or an LDH-based composite membrane that has undergone surface functionalization treatment.

5. An LDH-based aerosol collection filter membrane according to any one of claims 1-4, characterized in that: The aerosol collecting filter membrane is an LDH nanofiber membrane, which is an LDH thin film composed of LDH fibers with a diameter of 100-300 nm; the bimetallic elements of the LDH are Mg and Al, and the intercalation anion of the LDH is laurate; the LDH nanofiber membrane has undergone surface amylation.

6. The LDH-based aerosol collection filter membrane according to claim 5, characterized in that: The aerosol collecting filter membrane has a PM2.5 particle collection efficiency of over 99% under 80% RH conditions; and under 48 hours of continuous collection conditions, the PM2.5 collection efficiency remains above 98.7%.

7. An LDH-based aerosol collection filter membrane according to any one of claims 1-4, characterized in that, The aerosol collection filter membrane is an LDH-based composite membrane formed by superimposing and hot-pressing polyurethane as the bottom layer membrane and LDH-SiO2 composite membrane as the top layer membrane; wherein the LDH-SiO2 composite membrane is a composite membrane formed by coating a precursor of LDH and SiO2 onto a substrate polyester film; wherein the LDH is CaAl-LDH with benzoate intercalation.

8. The LDH-based aerosol collection filter membrane according to claim 7, characterized in that: The aerosol collecting filter membrane has a PM2.5 particle collection efficiency of over 96% in a high humidity environment of 80%RH, and the collection efficiency is still above 96% after 24 hours of continuous use.

9. The application of an LDH-based aerosol collection filter membrane according to claim 7, characterized in that: The aerosol collecting filter membrane is used in an industrial exhaust gas ventilation system, wherein the ambient temperature of the industrial exhaust gas ventilation system is set to 55 ℃, the relative humidity is set to 85%, and the particulate matter concentration (PM2.5) is set to 200 μg / m³. 3 PM10 was 300 μg / m³ 3 The gaseous pollutants were SO2 (30 ppm) and NO. x With a concentration of 25 ppm and toluene of 50 ppm, after 72 hours of continuous operation, the aerosol collection rate of the filter membrane remained above 96%.

10. A method for preparing an LDH-based aerosol collection filter membrane according to claim 5, characterized in that, Includes the following steps: MgAl-LDH powder with laurate intercalation was prepared by hydrothermal coprecipitation. LDH film preparation: The MgAl-LDH powder was dissolved in a water-ethanol mixed solvent to form an LDH solution, and then an LDH nanofiber film was formed by electrospinning. Surface functionalization treatment: The prepared LDH nanofiber membrane is immersed in an ethanol solution of APTES, heated at 50-60℃, washed with deionized water, and then dried to obtain an aminated LDH nanofiber membrane, which is the aerosol collecting filter membrane.

11. A method for preparing an LDH-based aerosol collection filter membrane according to claim 7, characterized in that, Includes the following steps: 1) Preparation of CaAl-LDH powder with benzoate intercalation; 2) Preparation of LDH-SiO2 composite film: Tetraethyl orthosilicate (TEOS) was used as SiO2 precursor to prepare SiO2 sol; CaAl-LDH powder and SiO2 sol formed a composite solution and formed a film on the substrate polyester film to obtain LDH-SiO2 composite film. 3) Lamination of polyurethane membrane and LDH-SiO2 composite membrane: Thermoplastic polyurethane is used as the bottom layer membrane. The LDH-SiO2 composite membrane and the polyurethane membrane are stacked and laminated using a hot press to obtain the composite aerosol collection filter membrane.